Формування аутофагосом та транскрипційна активність генів atg8 у клітинах кореня арабідопсису при розвитку аутофагії за умов мікрогравітації - Шадріна, Р.Ю.; Горюнова, І.І.; Блюм, Я.Б.; Ємець, А.І. (Доповіді НАН України, 2020)
Проведено морфологічний та цитологічний аналіз проростків коренів Arabidopsis thaliana і досліджено
процес індукції аутофагії в їх клітинах за умов мікрогравіатації. Встановлено істотне порушення розвитку коренів проростків і збільшення кількості аутофагосом в епідермальних клітинах перехідної зони кореня
на 6-ту добу вирощування за умов кліностатування, а також поступове зменшення їх кількості на 9-ту і
12-ту добу порівняно з контрольними рослинами, що може свідчити про адаптацію до умов зміненої гравітації. Результати транскрипційного аналізу активності генів родини atg8 (atg8a, atg8b, atg8c, atg8d, atg8e,
atg8f, atg8g, atg8h та atg8i), залучених до реалізації початкових етапів аутофагії (6—12 діб кліностатування), свідчать про залежний від часу характер змін рівня експресії більшості цих генів. Зокрема, зареєстровано підвищення рівня експресії генів atg8a, atg8c, atg8d на 6-ту добу, поступове їх зниження на 9-ту
добу і різке зниження після 12 діб кліностатування порівняно з контролем. Також встановлено значне (порівняно з контролем) підвищення рівня експресії генів atg8e, atg8f та atg8i на 6-, 9- та 12-ту добу. Отримані результати дають підставу стверджувати, що досліджувані гени atg8 є специфічними для реалізації початкових етапів аутофагії, індукованої мікрогравітацією. Morphological and cytological analyses of Arabidopsis thaliana seedlings roots growing under conditions mimicking
a microgravity has been performed. Moreover, we assessed the process of autophagy induction in cells
upon such conditions. Here, we report significant changes in the root development and the enhanced autophagosome
formation in epidermal cells in the transitional zone on the 6th day of cultivation upon conditions on a
rotating clinostat, as well as their gradual decrease on the 9th and 12th days, respectively, in comparison to control
plants. These changes may suggest the induction of the adaptive process to the microgravity conditions.
Family of atg8 genes (atg8a, atg8b, atg8c, atg8d, atg8e, atg8f, atg8g, atg8h, and atg8i) are involved in the implementation
of initial stages of autophagy. Transcriptional analysis of atg8 isoforms indicates clear time-dependent
expression changes (6-12 days of microgravity) in the majority of such genes. In particular, the increased
expression levels (atg8a, atg8c, atg8d) on the 6th day, a gradual decrease on the 9th day, and a significant decrease
after 12 days of growing on a clinostat have been observed in comparison to control. Our results de monstrate
the significantly elevated expression of atg8e, atg8f, and atg8i genes on the 6th, 9th, and 2th days. The
obtained data suggest that studied atg8 genes are specifically involved in autophagy induced by microgravity in
Arabidopsis thaliana.